2023
DOI: 10.1371/journal.pone.0289794
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with chronic systemic inflammatory disease in acute myocardial infarction

Hiroaki Yaginuma,
Yuichi Saito,
Takanori Sato
et al.

Abstract: Background Chronic systemic inflammatory diseases (CSIDs) such as rheumatoid arthritis (RA) are reportedly associated with an increased risk of ischemic cardiovascular events including acute myocardial infarction (MI). However, data are limited on clinical characteristics and ischemic and bleeding outcomes after acute MI in patients with CSIDs. Methods This bi-center registry included a total of 1001 patients with acute MI undergoing percutaneous coronary intervention. CSIDs included inflammatory rheumatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Prior research has demonstrated that individuals afflicted with inflammatory rheumatological conditions, such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), face an elevated risk of experiencing cardiovascular events, including myocardial infarction (MI) [6,7]. Moreover, when these patients develop coronary artery disease, including acute MI, it has been observed that their subsequent clinical outcomes are less favorable compared to those without such conditions [8,9]. This indicates that the presence of inflammatory rheumatological conditions may exacerbate the severity of coronary artery disease and its associated complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that individuals afflicted with inflammatory rheumatological conditions, such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), face an elevated risk of experiencing cardiovascular events, including myocardial infarction (MI) [6,7]. Moreover, when these patients develop coronary artery disease, including acute MI, it has been observed that their subsequent clinical outcomes are less favorable compared to those without such conditions [8,9]. This indicates that the presence of inflammatory rheumatological conditions may exacerbate the severity of coronary artery disease and its associated complications [3].…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Furthermore, AMI patients with CSIDs may have worse clinical outcomes after the hospital discharge. 12 …”
mentioning
confidence: 99%